![\begin{gathered} \text{Statement }\rightarrow\text{ Reason} \\ 7(x-1)=2(3x-2)\text{ }\rightarrow Given \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o05yhfo8s6eckdspki0drpnsqicqsyfbzu.png)
![7x-7=6x-4\text{ }\rightarrow\text{ Distributive property}](https://img.qammunity.org/2023/formulas/mathematics/college/op1fbmym63kc1dt647ps2fca3f7a09n2ly.png)
Beacuse to both sides of the equation you distribute the number that is outside the parentheses when making the product.
Then, you operate on both sides of the equation -7x, that is, you use the additive inverse of 7x
![\begin{gathered} 7x-7-7x=6x-4-7x \\ -7=-1x-4\text{ }\rightarrow\text{ additive inverse property} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rfajbjxpm389a4xs3j9r5x271kbi4w9ou2.png)
Then, you operate on both sides of the equation 4, that is, you use the add inverse of -4
![\begin{gathered} -7=-1x-4 \\ -7+4=-1x-4+4 \\ -3=-1x\text{ }\rightarrow\text{ additive inverse property} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1xfp501kajkc3l3vfmmza5bx1ynua713zx.png)
Finally,
![\begin{gathered} -3=-1x \\ (-3)/(-1)=x\text{ }\rightarrow\text{ Division property} \\ 3=x\text{ }\rightarrow\text{ Reflexive property} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/awxi5pm58d2blztzqwo9dc9wisp1rjmr0t.png)